(3GdbQGQGJ GdeGdjI h CKQgG aj JMOjO GdNjGQ GdGSJQGJjLj HGSJNOGe GSJQGJjLjI Gdfeh (B/s - (3GdefGUjQ, SajGf Ndjds ((3YeGf(B: s (3OGQ LdjS GdReGf(B, s, 2010)
(3GdbQGQG J GdeGdjI h bQGQGJ GdGSJKeGQ, GdYhGed GdebjOI ddCfTWI GdGSJKeGQjI h WHjYI eTGQjY GdGSJKeGQ, eNGWQ GdGSJKeGQ aj GdChQGb GdeGdjI, GdebheGJ GdCSGSjI dbQGQ GdGSJKeGQ, bQGQGJ GdJehjd h bQGQGJ JhRjY GdCQHGM, GdYdGbI Hjf GdbQGQGJ GdeGdjI h GdNjGQ GdGSJQGJjLj h JWHjbGJ GdGOGQI GdeGdjI aj eLGd GdGOGQI GdGSJQdGJjLjI, JWHjbGJ GdbjeI GdMGdjI aj UjGZI GSJQGJjLjI Gdfehs
(3HHdjhZQGajG(B: (3U(B.191-196s
Keywords: (3GdGSJKeGQs; (3GdJfejI GdEbJUGOjIs; (3GdeGdjIs